THE POTENTIAL OF THE ANTI-CRISIS CORE IN THE DEVELOPMENT OF A SYSTEM OF MEASURES FOR REALIZING OF THE INTER-PARADIGM TRANSITION - Shedyakov, Vladimir (Collection of scientific papers «ΛΌГOΣ», 2023)
Transitivity (especially, of the inter-paradigm level) manifests itself, in particular, in a series of crises. The anti-crisis core of society is formed by the elements of the development economy system around the moral-spiritual axis of each cultural-civilizational world. Main attributes are the environment and scientific, educational and industrial clusters of development. The more serious the choice facing society, the more justifiably one can state a key period of time. Socio-cultural and political-economic programming of development can be based on a flexible system of social automata and machines. The turn of the 2-3 millennia naturally revived questions about the optimization of the state, administrative, and political structure. But post-globalism gives a chance for success to each of the cultural-civilizational worlds, you just need to see the opportunity, be ready for it: grow your resource bases and social forms that allow you to perceive and produce strategic analysis, forecasting and designing global projects. This is especially important today, when the historical outlines of cultural-civilizational worlds are visibly restored in the world. The situation requires accuracy in determining the tree of goals and means, a flexible correlation of strategy, tactics and operational art. The optimization of actions during high-speed transformations during this period largely depends on the timeliness and accuracy of identifying the phases and characteristics of the crisis. Once upon a time, axial time endowed groups of humanity with leading characteristics. Now the global transition to a new social paradigm is superimposed on the return to the tasks of autochthonous, endogenous, import-substituting development as an element not only of the struggle to restore the economic foundation of sovereignty, but also to preserve one’s identity, a separate and independent contribution to the diversity of the ecumene [1-9]. Many options for influence lose their ultimate effectiveness: what is beneficial from the standpoint of immediate profitability can turn into a strategic loss. The potential for sustainability and development with participation in integration processes of a post-global level and quality is largely provided by a variety of life patterns and a combination of mastering the latest ways of life with the cultivation of innovative forms of basic value-sense complexes. So, if the Modern has accustomed to optimizing development through the unification of the model of life, then the diversity of features of new social structures focuses on the fundamental discrepancy between approaches and ways of optimization. Now the competition of cultural-civilizational worlds is a competition of models, forces and means: the higher the originality, the easier and more fully it is possible to take into account the features of the conditions, environment, and value-sense complexes, mental matrices, increasing competitive advantages and reducing risks. At the same time, changes are taking place not only in individual social institutions, but also in the very complex models of life and development, relationships and structures. After a period of inertia, there is a sharp degradation of the socio-political landscape of a number of countries, which is reflected in the world state of affairs. Finally, states claiming the status of regional leaders, and even significant global players, are moving away from many standards that were previously set from outside.